2001
DOI: 10.1038/sj.neo.7900135
|View full text |Cite
|
Sign up to set email alerts
|

Jun N-Terminal Kinase 1 Mediates Transcriptional Induction of Matrix Metal loproteinase 9 Expression

Abstract: Tumor cell invasion and metastasis require precise coordination of adherence to extracellular matrix (ECM) and controlled degradation of its components. Invasive cells secrete proteolytic enzymes known as matrix metalloproteinases (MMPs) which degrade specific basement membrane molecules. Expression of these enzymes is regulated by multiple signaling mechanisms, including the mitogen-activated protein kinase (MAPK) pathway. One of the terminal effectors of this signaling cascade is jun N-terminal kinase 1 (JNK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…Numerous studies have demonstrated that JNK1/2 and ERK1/2 transcriptionally regulate the expression of MMP-2 and MMP-9, which results in regulation of cell migration and invasion (25)(26)(27). In human bladder cancer cells, upregulation of the MAPK pathways may result in migration and regulation of the expression levels of MMPs (28).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that JNK1/2 and ERK1/2 transcriptionally regulate the expression of MMP-2 and MMP-9, which results in regulation of cell migration and invasion (25)(26)(27). In human bladder cancer cells, upregulation of the MAPK pathways may result in migration and regulation of the expression levels of MMPs (28).…”
Section: Discussionmentioning
confidence: 99%
“…Several signaling pathways activated downstream from the IGF-IR are also implicated in MMP upregulation. MMP-9 is upregulated by the mitogen-activated protein kinases (MAPKs) and the jun amino-terminal kinases (JNKs) in vascular smooth muscle cells (Cho et al, 2000), human epidermal keratinocytes (Zeigler et al, 1999;McCawley et al, 1999), and in numerous tumor types (Lakka et al, 2000;Gum et al, 1997;Crowe et al, 2001). In v-src transformed cells, which are invasive, MMP-2 is upregulated through constitutive, sustained activation of the MAPK kinase MEK1 (Kurata et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of a number of ets family members has been shown to increase CBP/p300 recruitment (10,16,20,27,30). We previously demonstrated that phosphorylation of the AP-1 protein c-jun is a potent activator of MMP-9 expression, suggesting a novel mechanism by which this modification may recruit coactivator proteins (8). These results suggest that phosphorylation of transcription factors and coactivators may provide a rapid means of regulating histone acetylation, chromatin unwinding, and induction of gene transcription.…”
mentioning
confidence: 86%